Vilnius and Kraków in Early Latin Poetry of Lithuania and in the History of St Casimir’s Cult: Parallels and Contrasts - Čiurinskas, Mintautas (Senoji Lietuvos literatūra, 2025)
This article aims to draw attention to early literary (poetic) texts dedicated to St Casimir, which were written both before the official approval of his cult in 1602 and immediately after. Most of them were composed and printed in Vilnius. In some of these texts, certain parallels between Vilnius and Kraków are highlighted, while at times, the contrast between the two cities is emphasised. In the article, this motif is discussed and interpreted within the broader context of the historical ties between Vilnius and Kraków, the history of Casimir’s canonisation, and of humanistic literature in general.The article is structured in three parts. The first, introductory, section discusses the historical connection between the two capitals, Vilnius and Kraków, which sooner or later was bound to emerge as a poetic theme. This happened even before the Union of Lublin, and perhaps the earliest example of this is a 1514 poem by Jacobus Piso. The fascinating intertwining of sixteenth-century interests of Kraków and Vilnius in the history of St Casimir’s canonisation and the succession of bishops are also explored.The second part examines the literary topos of the competition of the cities – certamen urbium – within the humanistic tradition of poetic creation. Its variations were also used by authors who worked in Lithuania (e.g., Petrus Roysius). This motif was also exploited in the earliest occasional works of the Jesuit academic milieu (Threnodiae, a collection of elegies on the death of Albertas Radvila, Vilnius, 1593). All of this brought this motif to the fore in neo-Latin poetry of Lithuania in the second half of the sixteenth century, even establishing a certain local literary tradition around it. It became the basis for using the motif of certamen urbium in occasional works dedicated to St Casimir, both in the earliest pre-canonisation works and those that flourished after his cult was officially recognised by the Church.All this is discussed in the third part of the article, in which three poetic examples are analysed in greater depth in relation to the aspect selected. The first example is the poem ‘Divi Casimiri ad Serenissimum Regem Stephanum Oratio’ by Adam Comlewicz, which appeared at the end of the 1579 collection Gratulationes, dedicated to the arrival of Stephen Báthory in Vilnius; in this poem, St Casimir descends from heaven and addresses the ruler. The connection between St Casimir and Vilnius is emphasised repeatedly in another poetry collection, Theatridium Poeticum Sanctissimo et Castissimo poetae D. Casimiro, which was published on the occasion of the canonisation celebrations in Vilnius (10–12 May 1604) and formed an autonomous section within the larger publication Theatrum S. Casimiri. In the middle of the collection, there is the poem ‘The Dispute Between the Two Cities Is Settled’ (Lis geminae componitur urbis) by Simonas Ugnievskis (Simon Ugniewski), which poetically immortalises the dispute between Kraków and Vilnius over a saint – a dispute that Vilnius wins by a decision of Rome. The third example is the short poem Epos de S. Casimiro Iagellonide, published in the same year of 1604 under the name of Jan Kraykowski, a student at the Vilnius Academy. In one of its episodes, the author mentions both St Hyacinth and St Casimir: the former as the pride of Kraków, the latter as the pride of Vilnius, linking their canonisation to the reign of Sigismund Vasa.The study suggests that in the early literary depictions of St Casimir, Vilnius played a special role as a place of eternal rest and a centre of worship. The poetic texts reflected the need of Lithuanian society for ‘one’s own’ saint – an aspect that is sometimes emphasised through contrast with Kraków and its saints. The facts from the prehistory of the canonisation reveal the historical basis for the literary parallels, contrasts, and a certain degree of rivalry between Vilnius and Kraków. This is an important feature of the early cult and conception of a local saint (indiges), one that should be noted when examining the later development of the cult in Lithuania and Poland, and, after 1621, throughout the world. A focus on the variants of certamen urbium as a common literary motif in literature dedicated to or dealing with St Casimir and its origins reveals the evolution of this motif and the early establishment of related variants in neo-Latin poetry in Lithuania (especially composed in the Jesuit academic milieu). To a certain extent, this article is a sequel to the article ‘Between the Cathedrals of Vilnius and Cracow: Some Historical Details in the Background of the Early Cult of St Casimir (Second and Third Decades of the Sixteenth Century)’, which appeared in Senoji Lietuvos literatūra, 2023, vol. 55.
Keywords: St Casimir; canonisation; St Hyacinth; Vilnius; Kraków; second half of the sixteenth century; 1604; Grand Duchy of Lithuania; neo-Latin poetry; certamen urbium